Prevalence, Risk Factors, Awareness, and Treatment and Control of Hypertension in Mafia Island, Tanzania - M. S. Muhamedhussein; Z. I. Nagri; K. P. Manji (International Journal of Hypertension)
Introduction. The prevalence of hypertension in Africa ranges from 29.7% in Cameroon to 47% in South Africa. Only 10% receive treatment in Cameroon while 32% are on medications in Ghana. Control rates vary from 0.4% to 16.8%. This study was done to assess prevalence, risk factors, awareness, treatment, and control of hypertension in Mafia Island, Tanzania, which has never been documented before, so that necessary interventions can be undertaken accordingly. Methodology. Data was collected through questionnaires and anthropometric measurements were taken. Descriptive statistics were done and potential correlations were analyzed. Results. Out of 570 adults who were included in the study, 154 (27%) were aged 41–50 and the male-to-female ratio was 1 : 1.05. Almost half (49.5%) of the participants fit into the criteria of hypertension. Out of the 118 participants who were aware of having hypertension, 68 (57.6%) were currently taking medication. From those taking medication, only 14 (20.6%) had controlled hypertension. Conclusion. This study tried to show the extent of hypertension and find out risk factors which could explain the high prevalence of hypertension. This is very alarming and a dire need to raise awareness through health education, availability of screening, and treating and follow-up should be given priority.